RAB39B Deficiency Impairs Learning and Memory Partially Through Compromising Autophagy - Niu, Mengxi; Zheng, Naizhen; Wang, Zijie; Gao, Yue; Luo, Xianghua; Chen, Zhicai; Fu, Xing; Wang, Yanyan; Wang, Ting; Liu, Manqing; Yao, Tingting; Yao, Peijie; et al. (Frontiers in Cell and Developmental Biology, 2020)
RAB39B is located on the X chromosome and encodes the RAB39B protein that belongs to the RAB family. Mutations in RAB39B are known to be associated with X-linked intellectual disability (XLID), Parkinson's disease, and autism. However, the patho/physiological functions of RAB39B remain largely unknown. In the present study, we established Rab39b knockout (KO) mice, which exhibited overall normal birth rate and morphologies as wild type mice. However, Rab39b deficiency led to reduced anxiety and impaired learning and memory in 2-month-old mice. Deletion of Rab39b resulted in impairments of synaptic structures and functions, with reductions in NMDA receptors in the postsynaptic density (PSD). RAB39B deficiency also compromised autophagic flux at basal level, which could be overridden by rapamycin-induced autophagy activation. Further, treatment with rapamycin partially rescued impaired memory and synaptic plasticity in Rab39b KO mice, without affecting the PSD distribution of NMDA receptors. Together, these results suggest that RAB39B plays an important role in regulating both autophagy and synapse formation, and that targeting autophagy may have potential for treating XLID caused by RAB39B loss-of-function mutations.